The Suitability of Building Permit Proposal and Implementation in Kecamatan Makale Kabupaten Tana Toraja - Panggoa, Risliana (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The development of a city is always influenced by the activities of the community which required land for the activities to take place. Limited land availability demanded a sound control mechanism to ensure the sustainability of the economic growth. The general society has not yet fully understood Building Permit (Izin Mendirikan Bangunan â€ IMB) as the instrument of control of spatial use, resulting in mismatches between the actual building and the one proposed in the IMB. This research aimed to find the factors driving the mismatches in the IMB implementation within the local Makale communityâ€™s understanding to concept of IMB. The study employed quantitative descriptive methods using frequency distribution tables and factor analysis. Factor analysis showed how lack of understanding and awareness in the concept of IMB, together with poor policy and execution by the local government have prevented the fully implementation. Some of the violations found included total building area, building function, Basic Structural Coefficient (Koefisien Dasar Bangunan â€ KDB), Building Line (Garis Sempadan Bangunan â€ GSB), and River Line (Garis Sempadan Sungai â€ GSS). The study concluded the need for IMB awareness promotion through socialization along with the technical procedures, enhancement of IMB monitoring and evaluation processes, finalization of IMB as regional regulation, and enforcement.